SOCIAL AND ECONOMIC RIGHTS OF CITIZENS IN UKRAINE: REGARDING THE ISSUE OF ENSURING IN A STATE OF WAR - Chepik-Trehubenko , Olha; Chernobuk , Valentyna (Collection of scientific papers «ΛΌГOΣ», 2025)
Armed conflicts are always accompanied by a negative impact on the level of provision for a decent life for the citizens of the state. First and foremost, the negative influence manifests in the area of realization of the social and economic rights of citizens – housing, nutrition, education, access to medical care, employment, and so forth. Therefore, in the current conditions – during the legal regime of martial law in Ukraine – the issue of ensuring social and economic rights of human beings and citizens holds particularly significant importance. Clearly, this state of affairs demands a comprehensive and ongoing search for new methods and modifications of existing strategies for ensuring social justice and protecting the rights of citizens, particularly social and economic rights.